2017
DOI: 10.1074/jbc.m117.775924
|View full text |Cite
|
Sign up to set email alerts
|

Computational and structural evidence for neurotransmitter-mediated modulation of the oligomeric states of human insulin in storage granules

Abstract: Human insulin is a pivotal protein hormone controlling metabolism, growth, and aging and whose malfunctioning underlies diabetes, some cancers, and neurodegeneration. Despite its central position in human physiology, the in vivo oligomeric state and conformation of insulin in its storage granules in the pancreas are not known. In contrast, many in vitro structures of hexamers of this hormone are available and fall into three conformational states: T6, T3Rf3, and R6. As there is strong evidence for accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…On top of this, the carboxylate group of the arginine is coordinating the zinc ion cofactor of the hexamer. Therefore this arginine binding mode corresponds to the starting crystallographic structure, 21 since the structure remained stable, and did not evolve significantly during the course of the simulation. Figure 7.…”
Section: Simulations Of Arginine Binding To the Insulin Hexamermentioning
confidence: 85%
“…On top of this, the carboxylate group of the arginine is coordinating the zinc ion cofactor of the hexamer. Therefore this arginine binding mode corresponds to the starting crystallographic structure, 21 since the structure remained stable, and did not evolve significantly during the course of the simulation. Figure 7.…”
Section: Simulations Of Arginine Binding To the Insulin Hexamermentioning
confidence: 85%
“…To assess the stability of the experimentally observed binding site of arginine, we also performed simulations at minimal ionic strength conditions of the crystallographic complex obtained in this work, which consists of an insulin dimer with one arginine in each of its monomers (System I). Since a crystallographic complex of the insulin hexamer exhibiting insulin-bound arginine molecules was previously obtained in the presence of arginine and serotonin, 21 we also explored the stability of the arginine binding site within the insulin hexamer. To this end, we performed simulations at minimal ionic strength conditions (i.e., only compensation of the protein charge) starting from the crystallographic structure (PDB 5MT9), after removal of the crystallographic serotonin molecules (system V).…”
Section: Simulationsmentioning
confidence: 99%
“…Since MD simulations as well as capillary electrophoresis and previous crystallographic experiments 21 indicated that insulin hexamerization appears to be possible in the presence of arginine at least at low ionic strength, we also probed the arginine binding to the insulin hexamer using MD simulations. Firstly, we assessed the stability of the crystallographic binding site for arginine in a T3R f 3 hexamer:serotonin:arginine complex.…”
Section: Simulations Of Arginine Binding To the Insulin Hexamermentioning
confidence: 99%
See 2 more Smart Citations